Polyhydroxyalkanoate-driven current generation via acetate by an anaerobic methanotrophic consortium. (1st August 2022) - Zhang, Xueqin; McIlroy, Simon J.; Vassilev, Igor; Rabiee, Hesamoddin; Plan, Manuel; Cai, Chen; Virdis, Bernardino; Tyson, Gene W.; Yuan, Zhiguo; Hu, Shihu
Highlights: A Methanoperedenceae- dominated methanotrophic consortium was able to respirate to electrodes. PHB was identified as energy source for the extracellular respiration of the consortium. Acetate was a likely intermediate from degradation of PHB and EPSs in the consortium. Methanoperedenceae interacted with Geobacter in the consortia via the diffusion of acetate. Abstract: Anaerobic oxidation of methane (AOM) is an important microbial process mitigating methane (CH4 ) emission from natural sediments. Anaerobic methanotrophic archaea (ANME) have been shown to mediate AOM coupled to the reduction of several compounds, either directly (i.e. nitrate, metal oxides) or in consortia with syntrophic bacterial partners (i.e. sulfate). However, the mechanisms underlying extracellular electron transfer (EET) between ANME and their bacterial partners or external electron acceptors are poorly understood. In this study, we investigated electron and carbon flow for an anaerobic methanotrophic consortium dominated by 'Candidatus Methanoperedens nitroreducens ' in a CH4 -fed microbial electrolysis cell (MEC). Acetate was identified as a likely intermediate for the methanotrophic consortium, which stimulated the growth of the known electroactive genus Geobacter . Electrochemical characterization, stoichiometric calculations of the system, along with stable isotope-based assays, revealed that acetate was not produced from CH4 directly. In the absence of CH4, current was still generated and the microbial community remained largely unchanged. A substantial portion of the generated current in the absence of CH4 was linked to the oxidation of the intracellular polyhydroxybutyrate (PHB) and the breakdown of extracellular polymeric substances (EPSs). The ability of ' Ca. M. nitroreducens' to use stored PHB as a carbon and energy source, and its ability to donate acetate as a diffusible electron carrier expands the known metabolic diversity of this lineage that likely underpins its success in natural systems. Graphical abstract: Image, graphical abstract